A case of pyometra and granulosa cell tumour in a sheep. Issue 4 (23rd July 2013) - Oultram, JW; Morgan, Lucy
<x xml:space="preserve">Abstract</x> This case report describes the diagnosis and treatment of pyometra and granulosa cell tumour in a pet ewe. It includes the use of simple imaging and blood testing to assist the diagnosis, the use of medical treatment in the control of the pyometra, a description of the surgical treatment in order to remove the granulosa cell tumour and the subsequent management of the wound dehiscence by insertion of a polypropylene mesh. The anaesthetic regimens are described and are techniques which can be used in practice. This particular case was followed to its full conclusion as the ewe was a valued pet; in the commercial breeding ewe the case work up would have ceased at an earlier point.